CAV-ES_m018p01 - Teste de Aptidão, 1969 - Centro de Audiovisual de Vitória – Espirito Santo - CAV/ES (1969)
Fotografias do curso de Comunicação e Recursos Audiovisuais; Testes: space relations; clerical; speed and accuracy; language usage; abstract reasoning; mechanical reasoning; numercial ability; verbal reasoning;